IMPLEMENTATION OF THE STEM LEARNING APPROACH IN PHYSICAL EDUCATION IN THE PROCESS OF STUDENT COGNITION DEVELOPMENT - Osada, Takako; Utami, Nissa Aulia Belistiana; Budiana, Dian (ASEAN Journal of Sport for Development and Peace, 2022)
In the 21st Century, students have to be able to think critically in solving problems of everyday life by way of scientific and normative thinking. It aligns with the STEM learning approach, which integrates four disciplines: Science, Technology, Engineering, and Mathematics. This study aimed to determine the impact of implementing the STEM learning approach in physical education on the development of students' cognitive processes at Lab school UPI Junior High School. The research method used is quasi-experimental, using pre-test and post-test designs. Forty-eight students participated. This study used the Cognitive Process Questionnaire in Physical Education (CPQPE) instrument, and the data were processed using SPSS. The results of this study are the probability value of the experimental group .205 .05, which means that the STEM learning approach has no significant impact on the level of students' cognitive development.